Racism and neo-Nazis in Internet: alsoin Latin America - Calvo-Buezas, Tomás (Universidad Pedagógica y Tecnológica de Colombia, 2014)
This essay reveals the relevance of internet in the dissemination of racial hatred through many different web pages of whatever ideology that link the radicals and fanatics of the global cyber village. The massacre of 76 people in Norway by Anders Behring Breivick, moved by hatred to Muslim immigrants and leftist activists from Europe, discovered the influence of the cyber communication and networks among radical and violent members of the extreme right. On the other side, the cyber networks played also a crucial role in the attacks of Muslim terrorism for the purpose of communication and recruitment of new terrorists. The essay shows some racist and neo-Nazi contents of pioneer web pages in United States, Spain and Latin America.